Draft genomic sequences of streptomyces misionensis ACT66 and streptomyces albidoflavus ACT77, bacteria with potential application for phytopathogen biocontrol - Pylro, Victor Satler; Dias, Armando Cavalcante Franco; Andreote, Fernando Dini; De Mello Varani, Alessandro [UNESP]; Andreote, Cristiane Cipolla Fasanella; de Figueiredo Ribeiro, Iron Amoreli; Kitano, Isabella Takahashi; de Almeida Bernardo, Eduardo Roberto (American Society for Microbiology, 2019)
Here, we report the draft genomic sequences and annotation of Streptomyces misionensis ACT66 and Streptomyces albidoflavus ACT77, which are two bacteria with potential application for phytopathogen biocontrol.